THE ROLE OF LITERACY HABITUATION IN IMPROVING CIVIC SKILLS OF STUDENTS AT SMK PRATAMA MULYA KARAWANG - Rizka Dwi Alfinda; Tarpan Suparman; Erwin Susanto (Institut Pendidikan Indonesia, 2026)
This study aims to examine the role of literacy habituation in improving students' civic skills at SMK Pratama Mulya Karawang. The approach used was descriptive qualitative, with data collection techniques including interviews, observation, and documentation. The results indicate that literacy habituation through morning reading activities, journal writing, thematic discussions, and the production of a school bulletin contributed positively to the development of critical thinking skills, the courage to express opinions, and active participation in social activities and school organizations. These findings reinforce the view that literacy, systematically cultivated in the educational environment, can be a strategic instrument in developing students' civic skills.